The learning relationship : psychoanalytic thinking in education - Youell, Biddy; Canham, Hamish; Tavistock Clinic (London : Karnac, 2006)
This book offers a psychoanalytic perspective on learning and teaching and on many of the issues which preoccupy those who work in educational institutions. It looks at the origins of learning in childrens early relationships and at factors which help and hinder the educational process in later childhood and adolescence. Amongst the topics addressed in the book are the significance of play and playfulness, the impact of change, separation, times of transition, bereavement, bullying and racism. The author has aimed to set well-established psychoanalytic ideas about learning within the context o.
'Where do babies come from?' What makes children want to learn? / Hamish Canham -- A theoretical overview : an introduction to psychoanalytic concepts and their application -- Play, playfulness, and learning -- Latency / Hamish Canham -- Adolescence -- Beginnings, endings, and times of transition -- Understanding behaviour : insight in the classroom and the value of observation -- Special educational needs -- Group dynamics in school -- Projective processes : gangs, bullying, and racism -- Families and schools -- Assessment, evaluation, and inspection -- Inclusion, exclusion, and self-exclusion.
"This volume is a collection of papers, each of which is a version of a lecture previously given as part of the Tavistock course, "Emotional factors in learning and teaching: counselling aspects in education"--p. 1.
Includes bibliographical references (p. 171-173) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Education -- Psychological aspects; Child analysis; Learning, Psychology of; EDUCATION -- Educational Psychology; Child analysis; Education -- Psychological aspects; Learning, Psychology of; Electronic books; Electronic books